2020
DOI: 10.1093/nar/gkaa388
|View full text |Cite
|
Sign up to set email alerts
|

3D-GNOME 2.0: a three-dimensional genome modeling engine for predicting structural variation-driven alterations of chromatin spatial structure in the human genome

Abstract: Structural variants (SVs) that alter DNA sequence emerge as a driving force involved in the reorganisation of DNA spatial folding, thus affecting gene transcription. In this work, we describe an improved version of our integrated web service for structural modeling of three-dimensional genome (3D-GNOME), which now incorporates all types of SVs to model changes to the reference 3D conformation of chromatin. In 3D-GNOME 2.0, the default reference 3D genome structure is generated using ChIA-PET data from the GM12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Besides, SVs have a more direct impact on the three-dimensional (3D) genome than SNVs [ 40 ]. Using a recently published algorithm [ 40 , 41 ], we found that four Tibetan-Han stratified SVs could lead to chromatin conformational changes (“ Methods ” section; Fig. 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, SVs have a more direct impact on the three-dimensional (3D) genome than SNVs [ 40 ]. Using a recently published algorithm [ 40 , 41 ], we found that four Tibetan-Han stratified SVs could lead to chromatin conformational changes (“ Methods ” section; Fig. 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the prediction of the overall rearrangement effect, it is possible to predict changes in 3-D genome structures as TADs and loops. The 3D-GNOME algorithm (Sadowski et al, 2019;Wlasnowolski et al, 2020) generates chromatin 3-D structures using a Monte Carlo approach based on chromatin conformation capture (3C) data. It uses high-quality CTCF or RNA polymerase II ChIA-PET data as a reference chromatin interaction pattern.…”
Section: Prediction Of Functional Consequences Of Rearrangementsmentioning
confidence: 99%
“…To assess if modular-territories in the regulatory network are representations of structure-based domains such as TADs and chromatin contact domains (CCDs), we investigated global and local CTCF-mediated 3D reconstruction (fig. S13A-B) (51,52). Locally, chromatin interaction analysis by paired-end tag sequencing (ChIA-PET) and CTCF-mediated reconstruction from several cell lines (51) revealed a clear overlap between CTCF-cluster graphs and network submodule territories (fig.…”
Section: S9a-b and Tablementioning
confidence: 99%